Attitudinal Correlates of HPV Vaccination in College Women. (June 2022) - Kasting, Monica L.; Christy, Shannon M.; Stout, Madison E.; Zimet, Gregory D.; Mosher, Catherine E.
This study examined associations between general attitudes toward seeking medical care, attitudes about vaccines/fear of shots, and human papillomavirus (HPV) vaccine uptake and intentions in college women. Hypothesized associations were framed by the Theory of Planned Behavior (TPB). Participants ( N  = 330, mean age = 18.9 years, 75% White) completed a one-time survey. The majority (61%; n  = 201) had received ≥1 HPV vaccine dose. Hierarchical logistic regression examined relationships between attitudes and vaccine uptake. Pearson correlation coefficients and Kruskal-Wallis tests examined associations between attitudes and vaccine intentions. Results were partially consistent with the TPB. In the final model, perceived benefits, but not fear of shots, were associated with vaccine uptake. Among the unvaccinated, perceived benefits, but not fear of shots, were associated with vaccine intentions. Provider recommendation was the strongest predictor of vaccine uptake. Findings suggest interventions incorporating discussion of perceived benefits and provider recommendation may improve HPV vaccine receipt among college women.